Nondestructive Evaluation of Special Defects Based on Ultrasound Metasurface - Zhao, Hualiang; Zhang, Chuanxin; He, Jiajie; Li, Ying; Li, Boyi; Jiang, Xue; Ta, Dean (Frontiers in Materials, 2022)
We demonstrate the nondestructive evaluation by means of directional ultrasound emitted from a planar metasurface. The ultrasound metasurface is designed to generate the collimated and directional ultrasound efficiently in a planar configuration, which is endowed with the full-2π-range phase manipulation ability and high transmittance up to 80%. We employ the directional emission based on the ultrasound metasurface to innovate the traditional nondestructive evaluation methods, benefited from the freely-controlled directivity and the superior fitness to sample surface of the planar metasurface. Merits of this innovative application are evidenced by the remarkable accuracy (higher than 98%) in the thickness evaluation, and precise detection (accuracy higher than 96%) of the special defect inside the V-shaped workpiece which is intractable to be inspected conventionally. The implementation of the metasurface-based directional ultrasound emission in the nondestructive evaluation bears the advantages of high coupling efficiency, superior fitness, high accuracy and applicability to special defect, providing new solutions to the challenges in conventional defect detection and promotes the development in the nondestructive evaluation applications.